The Influence of Artificial Intelligence in Using ChatGPT on Independent Behavior and Plagiarism of Students of the Islamic Religious Education Master's Study Program at UAS Kencong Jember - Nurhidayati, Titin; Rofiq, M. Nafiur (JOM, 2025)
Since artificial intelligence (AI) has significantly altered learning processes and methodologies, this article addresses the topic of using AI in student learning. This research aims to evaluate the statistical relationship between the use of AI and independent behavior, critical thinking, and acts of plagiarism. The research approach uses associative descriptive quantitative methods through surveys at Al-Falah As-Sunniyah University Kencong Jember. The research population consists of students who are familiar with the ChatGPT application, with research variables including ChatGPT use, independent behavior, and plagiarism. Data was collected through a questionnaire involving 50 respondents, then analyzed using descriptive and inferential statistics with the help of SPSS. Descriptive results show that 56% of respondents were men and 44% women, of which 68.8% of men were involved in plagiarism and 55.6% showed independent behavior. Inferential analysis revealed no significant relationship between ChatGPT use and plagiarism or self-directed behavior, based on Phi, Cramer's V, and Contingency Coefficient values.